The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/np300609u
|View full text |Cite
|
Sign up to set email alerts
|

Flavone Tetraglycosides and Benzyl Alcohol Glycosides from the Mongolian Medicinal Plant Dracocephalum ruyschiana

Abstract: From an extract of the aerial parts of Dracocephalum ruyschiana, five new flavone tetraglycosides, five new benzyl alcohol glycosides, and 19 known compounds were isolated. The tetraglycosides contain a 7-O-β-d-glucopyranosyl-(1→2)-β-d-glucopyranosyl-(1→2)-[α-l-rhamnopyranosyl-(1→6)]-β-d-glucopyranosyl moiety. The benzyl alcohol glycosides had acyl groups on their glycosyl or aglycone moieties. The compounds were tested for antioxidant activity using DPPH. Although the new compounds were not active, phenylprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…The acacetin glycosides, particularly their monoglycosides, have already been identified in aerial parts of other Dracocephalum species, for Dracocephalum ruyschiana or Dracocephalum foetidum [ 19 , 20 ] and also in transformed shoots of D. forrestii grown on agar-solidified media [ 22 ]. Several studies have reported that acacetin glycoside derivatives inhibited enzymes such as acetylcholinesterase and hyaluronidase [ 20 , 53 ]. In addition, these compounds are expected to have antioxidant, anti-inflammatory, and anti-cancer activity [ 20 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The acacetin glycosides, particularly their monoglycosides, have already been identified in aerial parts of other Dracocephalum species, for Dracocephalum ruyschiana or Dracocephalum foetidum [ 19 , 20 ] and also in transformed shoots of D. forrestii grown on agar-solidified media [ 22 ]. Several studies have reported that acacetin glycoside derivatives inhibited enzymes such as acetylcholinesterase and hyaluronidase [ 20 , 53 ]. In addition, these compounds are expected to have antioxidant, anti-inflammatory, and anti-cancer activity [ 20 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that acacetin glycoside derivatives inhibited enzymes such as acetylcholinesterase and hyaluronidase [ 20 , 53 ]. In addition, these compounds are expected to have antioxidant, anti-inflammatory, and anti-cancer activity [ 20 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous phytochemical investigation has revealed that flavonoids and terpenoids were the major constituents of genus Dracocephalum [ 11 ]. Biological studies on these flavonoids have revealed their broad pharmacological activities, especially antioxidant, immunomodulatory, and cytotoxic activities, as well as cardiovascular protective effects [ 11 , 13 , 14 , 15 , 38 , 39 ]. Trypanocidal diterpenoids with icetexane and octahydroindene skeletons were discovered from the whole plants of D. komarovi [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some plants in this genus, including D. moldavica and D. tanguticum , are broadly used in traditional medicine for gastropathy, tracheitis, and cardiovascular disease in Xinjiang and Tibet [ 11 , 12 ]. Typical metabolites in the plants of this genus were flavonoids and terpenoids [ 13 , 14 , 15 , 16 ]. Monoterpenes limonene and α-terpineol might be responsible for antinociceptive properties in the essential oil of D. kotschyi [ 17 ].…”
Section: Introductionmentioning
confidence: 99%